Pertumbuhan dan hasil empat genotipe sorgum manis dengan perlakuan dosis mikoriza arbuskuler - Riyati, Rati; Nurngaini, Nurngaini (Jurnal Agrivet, 2014)
Sorghum Sorghum bicolor L. Moench is a crop cereal grains which is included in Gramineae or grasses. In Indonesia, currently sorghum crop brings new opportunity to be developed as a food crop, feed and producing bioethanol. The study aims to examine the interaction between the type of sweet sorghum genotypes and arbuscular micorhize doses, approppriate micorhize dose and sweet sorghum response to micorhize treatment. The research was conducted through a field experiment with a split plot design with sorgum genotypes as the main plot consisting of three genotypes which is G1=HZ-30, G2=Mandau, G3=Patir 9, and G4=Patir 3. As the sub plot is the micorhize dose consisting of three doses namely: D1=0 g/plant, D2=5 g/plant, and D3=10 g/plant with three replications. Observation were made on growth parameters which are plant height, stem diameter, leaf area, root volume, root dry weight, dry weight of the canopy and the dry weight of the seeds per hectare. Yield parameters consist of: essay panicle length and dry weight of seeds per hectare. The data is then analyzed its variance at 5% level of significance, and to find out the differences between treatments Duncan’s Multiple Range Test was conducted at 5% level of significance. The result shows: 1. An interaction is found between the treatment of genotypes and micorhize doses to both vegetative and generative growth of sweet sorghum. 2. Micorhizal dose treatment has not significant affect on all generative growth of sweet sorghum genotypes. 3. HZ-30 genotype with no micorhizal treatment produces the heaviest dry weight of seeds per hectare. Sorgum (Sorghum bicolor L. Moench ) merupakan tanaman serealia biji-bijian yang termasuk famili Graminaea atau rerumputan. Di Indonesia, saat ini tanaman sorgum memberi peluang untuk dikembangkan sebagai tanaman pangan, pakan dan penghasil bioetanol (bioenergi). Penelitian bertujuan mengkaji adanya interaksi antara macam genotip sorgum manis dengan dosis mikorisa arbuskular, dosis mikorisa yang sesuai, dan sorgum manis yang respon terhadap mikoriza. Penelitian dilaksanakan dengan percobaan lapangan dengan rancangan split plot sebagai main plot adalah genotip sorgum, G1 : HZ-30,G2 : Mandau,G3 : Patir 9, danG4 : Patir 3 dan sub plot dosis mikoriza, D1 : 0 g/tanaman,D2 : 5 g/tanaman, dan D3 : 10 g/tanaman dengan tiga ulangan. Pengamatan dilakukan pada parameter pertumbuhan yakni : tinggi tanaman, diameter batang, luas daun,diameter batang, volume akar, bobot kering akar, bobot kering tajuk, dan bobot kering tanaman.Parameter hasil diantaranya : panjang karangan malai, dan bobot biji kering per hektar. Data dianalisis keragamannya pada jenjang 5 % dan untuk mengetahui perbedaan antar perlakuan dilakukan uji jarak berganda Duncan jenjang 5 %. Hasil penelitian menunjukkan : 1.Terdapat interaksi antara perlakuan genotip dengan dosis mikorisa pada semua pertumbuhan vegetatif dan generatif sorgum manis. 2.Perlakuan dosis mikoriza belum berpengaruh nyata pada semua pertumbuhan vegetatif genotip sorgum manis. 3. Genotip HZ-30 dengan tanpa perlakuan mikoriza menghasilhan bobot biji kering / hektar yang terbesar.